Prevalence and Associated Factors of Overweight and Obesity among High School Adolescents in Bahir Dar City, Northwest, Ethiopia: A Cross-Sectional Study - Mulugebeya Worku; Zemichael Gizaw; Aysheshim Kassahun Belew; Alemakef Wagnew; Melkamu Tamir Hunegnaw (Journal of Obesity)
Background. Overweight and obesity can be defined as excessive and abnormal fat deposition in our bodies. A body mass index for age of Z scores +2 to +3 was classified as overweight, whereas BMI for age >+3 Z-score was considered as obesity. Overweight and obesity in adolescents are a major health problem in low-income countries like Ethiopia. However, there is not well-established data on adolescents’ overweight and obesity. Therefore, this study assessed the prevalence and associated factors of overweight and obesity among high school adolescents in Bahir Dar city, northwest of Ethiopia. Methods. An institution-based cross-sectional study was conducted from October 30 to November 30/2019 among 551 high school adolescents. Data were collected using a self-administrative questionnaire. Weight and height were measured by trained health professionals. World Health Organization AnthroPlus software was used to analyze anthropometric data into body mass index for age with z-score to ascertained overweight and obesity. Data were entered using Epi Info version 3.5.3 and transferred to SPSS version 22 for further analysis. Frequency and percentage were presented using tables and figures. A bivariable and multivariable logistic regression analysis was performed to determine the association between the dependent and independent variables. Adjusted odds ratio with 95% CI and p<0.05 were used to dictate statistical significance for overweight and obesity. Result. In this study, 522 high school adolescents aged 10–19 years were selected using a simple random sampling technique with a response rate of 94.74%. The mean age of the respondents was 17 years with SD ± 1.41. The overall prevalence of overweight and obesity was 12.5% (95% CI: 9.6, 15.2). Males (13.3%) were more than females (11.5%), being overweight and obese. Having self-employed mothers (AOR: 4.57; 95% CI: 1.06, 19.78), having government-employed mothers (AOR: 6.49; 95% CI: 1.96, 21.54), and having school feeding habit (AOR: 0.44; 95% CI: 0.26, 0.76) were factors associated with overweight/obesity among high school adolescents. Conclusion. The prevalence of overweight/obesity in the current study was high. Adolescents having self-employed mothers, adolescents having government-employed mothers, and students having school feeding habits were significant factors of overweight and obesity. Therefore, more emphasis will be given to adolescents having self- and government-employed mothers and adolescents having school feeding habit.